Safe composite solid electrolyte and preparation method thereof
Through the preparation method of composite solid electrolytes of AIBN, PEGDA and LLZO, combined with TFEC:FBN-LiTFSI ion conduction buffer layer, the safety and mechanical properties of traditional liquid electrolytes are solved, and the combination of high ionic conductivity and flame retardant characteristics is achieved. Solid electrolyte improves the safety and stability of the battery.
Patent Information
- Application Number
- CN202411200736.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-24
AI Technical Summary
Traditional liquid electrolytes have problems such as volatility, corrosion, and liquid leakage, which affects the safety and performance of batteries. The mechanical processing performance of inorganic electrolytes is poor, affecting industrial application.
The composite solid electrolyte preparation method of materials such as AIBN, PEGDA and LLZO is adopted to form a safe composite solid electrolyte with high ionic conductivity through mixing and heat treatment, and combined with TFEC:FBN-LiTFSI as the ion conduction buffer layer to enhance mechanical properties and stability.
High ionic conductivity and good flame retardant properties are achieved, which improves the safety and stability of the battery, simplifies the preparation process and reduces costs.
Smart Images

Figure CN119181843A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a safe composite solid electrolyte and a preparation method thereof. Background Art
[0002] In the fields of modern electricity, electronics, photovoltaics, etc., the demand for energy storage devices is growing. Especially in portable electronic devices, electric vehicles and renewable energy storage systems, solid-state batteries have become an emerging energy storage device that has received widespread attention. The electrolyte, as a key component of the sealed battery system, directly affects the performance and safety of the battery. Traditional liquid electrolytes have many problems such as volatilization, corrosion, and leakage. These problems not only limit the commercial application scope of liquid electrolyte batteries, but may also cause safety accidents and pose a threat to the environment and personal safety. Solid-state electrolytes have become the best choice to solve the problem of liquid electrolytes because of their many advantages such as small size, high stability, non-volatility, non-flammability, and non-corrosion.
[0003] The key to solid-state batteries lies in the optimization of solid electrolytes with high ionic conductivity. Due to the poor mechanical processing properties and interface contact of traditional inorganic electrolytes, there are great problems in industrial applications. Inorganic-organic composite electrolytes are currently a way to solve the mechanical processing performance problem, but the addition of organic polymers will reduce ionic conductivity and affect battery performance.
[0004] In view of this, it is necessary to design an improved safe composite solid electrolyte and a preparation method thereof to solve the above problems. Summary of the invention
[0005] In view of the above-mentioned defects of the prior art, the object of the present invention is to provide a safe composite solid electrolyte and a preparation method thereof. The composite electrolyte has high ionic conductivity and good flame retardant properties after curing and is highly safe.
[0006] To achieve the above object, the present invention provides a method for preparing a safe composite solid electrolyte, comprising the following steps:
[0007] S1. AIBN (azobisisobutyronitrile) and an ion conductive buffer layer are mixed until AIBN is dissolved, and PEGDA (polyethylene glycol diacrylate) is added and dispersed uniformly to obtain a dispersion;
[0008] S2. Add LLZO (lithium lanthanum zirconium oxygen electrolyte Li7La3Zr2O) to the dispersion obtained in step S1. 12 ) powder, and grinding to obtain an electrolyte precursor;
[0009] S3. The electrolyte precursor obtained in step S2 is coated on a current collector, and heat-treated at a predetermined temperature to obtain a safe composite solid electrolyte.
[0010] As a further improvement of the present invention, in step S1, the mass ratio of AIBN, PEGDA and ion-conducting buffer layer is (2-3):20:100.
[0011] Furthermore, the ion-conducting buffer layer is TFEC:FBN-LiTFSI, which is a composite liquid system composed of LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), FBN (4-fluorobenzonitrile), and TFEC (bis(2,2,2-trifluoroethyl) carbonate).
[0012] As a further improvement of the present invention, in step S2, the particle size of the LLZO powder is 10-20 μm, the mass ratio of the LLZO powder is 60wt%-80wt%, and the grinding time is 30-40 min.
[0013] As a further improvement of the present invention, in step S3, the temperature of the heat treatment is 55-65°C, and the time is 30min-60min.
[0014] Furthermore, the material of the current collector is aluminum foil. The thickness of the electrolyte precursor coated on the current collector is 60-100 μm.
[0015] The present invention also provides a safe composite solid electrolyte, which is prepared by the preparation method of the safe composite solid electrolyte.
[0016] The beneficial effects of the present invention are:
[0017] The present invention provides a safe composite solid electrolyte and a preparation method thereof, wherein AIBN, PEGDA, an ion conductive buffer layer and LLZO are uniformly mixed in proportion, then coated on the surface of a current collector, and the curing time is controlled by heating to finally obtain a safe composite solid electrolyte. The composite electrolyte of the present invention maintains a relatively high ionic conductivity after curing, which meets the application requirements in batteries; and maintains a certain mechanical flexibility after curing, will not peel off from the current collector, has good flame retardant properties, and is highly safe.
[0018] The present invention uses TFEC:FBN-LiTFSI as an ion conduction buffer layer to provide an efficient ion transmission channel in the cross-linked polymer network and maintain a high ion conductivity. The solidified PEGDA cross-linked network can enhance the tensile strength and elastic modulus of the electrolyte, making it more durable during battery assembly and use. FBN has good interface compatibility with lithium metal or other battery components, which helps to improve the overall performance and stability of the battery. Combined with the cross-linked polymer network, the mechanical properties of the solid electrolyte can be improved. LLZO powder can be used as a filler to improve the safety of solid-state batteries and the ionic conductivity of the electrolyte, thereby improving the overall performance of the battery.
[0019] The safe composite solid electrolyte provided by the present invention has the advantages of simple preparation process, low preparation cost, etc., can be widely used in battery manufacturing, and can effectively improve the safety and stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a bending diagram of the safe composite solid electrolyte prepared in Example 1 of the present invention.
[0021] Figure 2 This is a diagram showing the coating effect of the electrolyte precursor in Example 1 of the present invention. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0023] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0024] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0025] The present invention provides a method for preparing a safe composite solid electrolyte, comprising the following steps:
[0026] S1. AIBN and an ion conductive buffer layer are mixed until AIBN is dissolved, and PEGDA is added to disperse them uniformly to obtain a dispersion.
[0027] Specifically, the mass ratio of AIBN, PEGDA and ion-conducting buffer layer is (2-3): 20: 100. The ion-conducting buffer layer is TFEC: FBN-LiTFSI, which is a composite liquid system composed of LiTFSI, FBN and TFEC. FBN is first melted into a liquid, and then TFEC and liquid FBN are evenly mixed to obtain a composite liquid solvent. LiTFSI is added to the composite liquid solvent and evenly dispersed to obtain the ion-conducting buffer layer TFEC: FBN-LiTFSI.
[0028] AIBN acts as a free radical initiator. The decomposition of AIBN can generate free radicals that can initiate free radical polymerization of double bonds in PEGDA to form a cross-linked polymer network. This cross-linked structure helps to improve the mechanical properties of the electrolyte. The ion-conducting buffer layer formed by the combination of TFEC, FBN and LiTFSI can provide a good ion transport channel while maintaining the mechanical stability of the electrolyte.
[0029] The appropriate proportion of AIBN can trigger the polymerization reaction of PEGDA, avoiding the generation of too many free radicals that lead to too fast or uneven polymerization. As a crosslinker, PEGDA has a higher proportion than AIBN, which helps to form a crosslinked network of sufficient strength. TFEC:FBN-LiTFSI serves as an ion conduction buffer layer, connecting LLZO particles to construct a lithium ion transmission channel, ensuring that the electrolyte has good ionic conductivity.
[0030] S2. Add LLZO powder to the dispersion obtained in step S1, and grind to obtain an electrolyte precursor.
[0031] Specifically, the particle size of the LLZO powder is 10 to 20 μm, the mass ratio of the LLZO powder is 60 wt % to 80 wt %, and the grinding time is 30 to 40 min.
[0032] LLZO has good ionic conductivity, chemical stability and thermal stability. Controlling the mass ratio of LLZO powder in the electrolyte precursor to 60wt% to 80wt% can improve the ion transport performance and mechanical strength of the electrolyte.
[0033] S3. The electrolyte precursor obtained in step S2 is coated on the current collector, and heat-treated at a predetermined temperature to obtain a safe composite solid electrolyte.
[0034] Specifically, the material of the current collector is aluminum foil, which has good chemical stability; the heat treatment temperature is 55-65°C and the time is 30min-60min, ensuring that AIBN can effectively decompose to produce free radicals while avoiding excessive temperature that causes material degradation or structural damage. The appropriate temperature can promote the cross-linking reaction of PEGDA to form a uniform solid electrolyte layer; the thickness of the electrolyte precursor coated on the current collector is 60-100μm, and the appropriate thickness can balance the battery internal resistance and mechanical strength. A too thin layer may result in insufficient mechanical properties, while an overly thick layer may increase the battery internal resistance and affect the battery's charge and discharge performance.
[0035] The purpose of the heat treatment is to cure the electrolyte precursor coated on the current collector, crosslinking the PEGDA by initiating a free radical polymerization reaction to form a solid electrolyte. The heat treatment also helps to improve the ionic conductivity and mechanical properties of the electrolyte while removing solvents and other volatile components.
[0036] The safe composite solid electrolyte and its preparation method provided by the present invention are described below with reference to specific embodiments.
[0037] Example 1
[0038] Embodiment 1 provides a method for preparing a safe composite solid electrolyte, comprising the following steps:
[0039] S1. According to the mass fraction, 2 parts of AIBN and 100 parts of ion conductive buffer layer TFEC: FBN-LiTFSI are mixed until AIBN is dissolved, and 20 parts of PEGDA are added and dispersed evenly to obtain a dispersion; the preparation method of the ion conductive buffer layer FBN-LiTFSI comprises the following steps:
[0040] First, 4-fluorobenzonitrile (FBN) is melted into a liquid at 60°C, and then bis(2,2,2-trifluoroethyl) carbonate (TFEC) and liquid 4-fluorobenzonitrile (FBN) are uniformly mixed to obtain a composite liquid solvent; wherein the volume ratio of bis(2,2,2-trifluoroethyl) carbonate (TFEC) to 4-fluorobenzonitrile (FBN) is 2:8;
[0041] 1Mol / L LiTFSI (lithium bis(trifluoromethanesulfonyl)imide) is added to the composite liquid solvent and dispersed evenly to obtain an ion-conducting buffer layer TFEC:FBN-LiTFSI.
[0042] S2: Take 40 parts of the dispersion, add 60 parts of LLZO powder, and grind for 30 minutes to obtain the electrolyte precursor.
[0043] S3. The electrolyte precursor is coated on the current collector and heat treated at 60° C. for 1 h to obtain a safe composite solid electrolyte.
[0044] Figure 1 This is a bending diagram of the safe composite solid electrolyte prepared in Example 1. Figure 2 This is a coating effect diagram. It can be seen that the composite solid electrolyte gradually changes from liquid to solid during the preparation process and has a certain flexibility.
[0045] Example 2 and Comparative Examples 1-3
[0046] Example 2 and Comparative Examples 1-3 respectively provide a method for preparing a safe composite solid electrolyte. Compared with Example 1, the only difference is that the mass fraction of AIBN is different, resulting in different curing time, as shown in Table 1. Other experimental parameters and conditions are basically the same as those in Example 1 and are not repeated here.
[0047] Examples 3-4 and Comparative Examples 4-5
[0048] Examples 3-4 and Comparative Examples 4-5 respectively provide a method for preparing a safe composite solid electrolyte. Compared with Example 1, the only difference is that the mass ratio of LLZO powder is different, as shown in Table 1. Other experimental parameters and conditions are basically the same as those in Example 1 and will not be repeated here.
[0049] Table 1 Parameters and performance of the embodiments and comparative examples
[0050]
[0051] “--” means no valid results.
[0052] As can be seen from Table 1, the content of AIBN affects the curing speed, and the content of LLZO affects the viscosity, which in turn affects the curing effect, including film-forming properties and ionic conductivity. No AIBN was added in Comparative Example 1, resulting in failure to cure; a small amount of AIBN was added in Comparative Example 2, resulting in a long curing time; excessive AIBN was added in Comparative Example 3, resulting in too fast a curing speed, and uneven agglomerates were formed before coating, affecting the coating effect; the LLZO powder content in Comparative Example 4 was reduced, the viscosity was significantly reduced, and liquid was separated during the curing process; the LLZO powder content in Comparative Example 5 increased, the viscosity increased, and uniform coating could not be achieved; the prepared solid electrolyte membranes were flame retardant because of LLZO and the ion-conducting buffer layer TFEC:FBN-LiTFSI.
[0053] The mechanical properties of the safe composite solid electrolytes prepared in Examples 1-4 were tested, and the results are shown in Table 2.
[0054] Table 2 Mechanical properties test results of Examples 1-4
[0055] project Tensile strength(Mpa) Average elastic modulus (Mpa) Example 1 1.7 3102 Example 2 1.4 2202 Comparative Example 3 0.9 2943 Example 4 0.4 2798
[0056] It can be seen from Table 2 that the safe composite solid electrolyte prepared by the present invention has a certain tensile strength. As the LLZO content gradually increases, the polymer ratio is relatively reduced, resulting in a decrease in tensile strength, but it can still meet the use requirements, can prevent mechanical damage during battery operation, and ensure that it will not break when bent or deformed; at the same time, the solid electrolyte also has a certain elastic modulus, which can ensure that the material adapts to the stress in the solid-state battery preparation process, which is very important for maintaining the stability of the battery structure.
[0057] In summary, the safe composite solid electrolyte provided by the present invention can maintain a high ionic conductivity after solidification, which meets the application requirements in the battery; and maintain a certain mechanical flexibility after solidification, and will not peel off from the current collector, avoiding the electrolyte and the current collector from peeling off due to mechanical stress during use, thereby extending the service life; at the same time, the composite solid electrolyte has good flame retardant properties and high safety. The present invention has the advantages of simple preparation process, low preparation cost, etc., can be widely used in battery manufacturing, and can effectively improve the safety and stability of the battery.
[0058] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a safe composite solid electrolyte, characterized in that: The following steps are involved: S1. AIBN and the ion conductive buffer layer are mixed until AIBN is dissolved, and PEGDA is added and dispersed uniformly to obtain a dispersion; S2. Add LLZO powder to the dispersion obtained in step S1, and grind to obtain an electrolyte precursor; S3. The electrolyte precursor obtained in step S2 is coated on a current collector, and heat-treated at a predetermined temperature to obtain a safe composite solid electrolyte.
2. The method for preparing a safe composite solid electrolyte according to claim 1, characterized in that: In step S1, the mass ratio of AIBN, PEGDA and ion-conducting buffer layer is (2-3):20:
100.
3. The method for preparing a safe composite solid electrolyte according to claim 2, characterized in that: The ion-conducting buffer layer is TFEC:FBN-LiTFSI, which is a composite liquid system composed of LiTFSI, FBN and TFEC.
4. The method for preparing a safe composite solid electrolyte according to claim 1, characterized in that: In step S2, the particle size of the LLZO powder is 10 to 20 μm.
5. The method for preparing a safe composite solid electrolyte according to claim 4, characterized in that: The mass ratio of the LLZO powder is 60wt% to 80wt%.
6. The method for preparing a safe composite solid electrolyte according to claim 4, characterized in that: The grinding time is 30 to 40 minutes.
7. The method for preparing a safe composite solid electrolyte according to claim 1, characterized in that: In step S3, the heat treatment temperature is 55-65°C and the time is 30-60 minutes.
8. The method for preparing a safe composite solid electrolyte according to claim 7, characterized in that: The material of the current collector is aluminum foil.
9. The method for preparing a safe composite solid electrolyte according to claim 7, characterized in that: The thickness of the electrolyte precursor coated on the current collector is 60-100 μm.
10. A safe composite solid electrolyte, characterized in that: The safe composite solid electrolyte is prepared by the preparation method of any one of claims 1 to 9.
